Crafting an Amish biomedical landscape (Medicine Anthropology Theory, 2020)
Within their pluralistic system of health care, the Amish make medical decisions influenced by cultural practice: a call for adherents to separate themselves from the outside world and to yield to the group. Using ethnographic research, this article discusses one aspect of the relationship between Amish communities near Lancaster, Pennsylvania, and a pediatric genetics clinic that has reformed the ways it mobilizes biomedicine in order to engage this community. Despite local Amish reticence to participate in biomedical systems, three elements discussed here are among those that help shape successful relationships between Amish families and the clinic: a carefully crafted physical space, a conceptualization of genetic medicine as skilled work, and a consideration for culturally appropriate use of time. Amish spaces of practice open to incorporate the clinic as biomedical spaces labor to incorporate Amish practice. The result is an emergent therapeutic landscape developing as a response to group social practice.